Development of QR Code-Based Mufradat Song Media for Arabic Language Learning - Syamsul Anam; Asep Maulana; Lailatul Usriyah; Emil Naila Sa'da Dinina (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
Abstract This research is motivated by the low interest and difficulty of students in memorizing Arabic vocabulary, especially among students who graduated from general elementary schools, who are not accustomed to learning Arabic since childhood. This study aims to develop a song-based Arabic language learning media to improve vocabulary memorization competency (mufradat) of grade VII students of MTs Negeri 9 Banyuwangi and test its feasibility based on the assessment of media experts and material experts. This study uses a Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The data collection instrument is a validation questionnaire from media experts and material experts with a Likert scale. The results show that the product developed is a pocket book of vocabulary songs equipped with a QR Code to access audio recordings. The results of the media expert validation obtained a percentage of 98% with a very feasible category, while the validation of material experts also reached 98% with a very feasible category. These findings confirm that the song-based learning media developed meet the feasibility criteria from both technical and material aspects. This research contributes to the development of innovative audio and visual-based learning media that can be used as an alternative for learning Arabic that is more interesting, interactive, and effective for students at the junior high school level. Keywords: Learning Media, Vocabulary Memorization Ability, Vocabulary Songs